The Effect of Expected Effective Corporate Tax Rates on Incremental Financing Decisions - Gropp, Reint (Washington, D.C. : International Monetary Fund, 1997)
This paper uses U.S. panel data to estimate the effect of expected effective corporate tax rates on firm's leverage. The paper directly estimates expected corporate tax rates using rational expectations. The estimated measures of the expected effective tax rates of firms are related to a continuous measure of incremental debt financing. The paper finds that expected effective tax rates are significantly and positively related to a higher level of debt financing. Simulations suggest that debt issues would double if firms were unable to shield profits and actually faced the statutory tax rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet